RUST WEB DEVELOPMENT WITH ROCKET a practical guide to starting your journey in Rust web development using the Rocket framework - Murti, Karuna (PACKT PUBLISHING LIMITED, 2022)
Explore the world of Rocket-fueled web application development and the power of the Rust programming language Key Features Discover solutions to the common problems faced while creating web applications with Rocket Learn everything about Rust, from structs and crates to generics and debugging Combine Rust and Rocket to create, test, and deploy a full-featured web app Book Description Looking for a fast, powerful, and intuitive framework to build web applications? This Rust book will help you kickstart your web development journey and take your Rust programming skills to the next level as you uncover the power of Rocket - a fast, flexible, and fun framework powered by Rust. Rust Web Development with Rocket wastes no time in getting you up to speed with what Rust is and how to use it. You'll discover what makes it so productive and reliable, eventually mastering all of the concepts you need to play with the Rocket framework while developing a wide set of web development skills. Throughout this book, you'll be able to walk through a hands-on project, covering everything that goes into making advanced web applications, and get to grips with the ins and outs of Rocket development, including error handling, Rust vectors, and wrappers. You'll also learn how to use synchronous and asynchronous programming to improve application performance and make processing user content easy. By the end of the book, you'll have answers to all your questions about creating a web application using the Rust language and the Rocket web framework. What you will learn Master the basics of Rust, such as its syntax, packages, and tools Get to grips with Rocket's tooling and ecosystem Extend your Rocket applications using Rust and third-party libraries Create a full-fledged web app with Rocket that handles user content Write pattern-matching logic and handle Rust object lifetimes Use APIs and async programming to make your apps secure and reliable Test your Rocket application and deploy it to production Containerize and scale your applications for maximum efficiency Who this book is for This web development book is for software engineers who want to learn how to use the Rocket framework to build web applications. Although not mandatory, basic knowledge of the Rust programming language will help you understand the topics covered easily.